Települési versenyképesség, települési siker - Józsa, Klára (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The success is variable and complex. Recognation of local talent, mayor of the settlement, cooperation of population, intellectual capital, firms are important to success. This elements are more important in a small village’s life, particularly, when this settlement is a young small village as Remeteszölős.